Long-term effect of Raw Sewage Application on Chemical Composition of Vegetables Grown on Sandy Soils of Western Rajasthan. (Indian Journal of Arid Horticulture, 2013)
Sewage water from Nathusar drain irrigating the vegetable crops in Shriramsar and Sujandesar area was collected  and analysed for the various chemical constituents. Five vegetables of winter season Spinach, Fenugreek, Cauliflower,  Cabbage, and Radish and five vegetables of summer season Bottle gourd, Ridge gourd, Amaranth, Cucumber and Brinjal  from the fields irrigated with sewage were collected at the stage to be picked up for marketing. The sewage water of Nathusar  drain of Bikaner city contain higher values of EC, adjusted SAR, TSS and BOD, however, the metallic cations content were  below the recommended maximum permissible concentrations. Ahigher inorganic and organic loading of sewage water and  metallic cations buildup particularly Zn, Cu and Fe in vegetables under study call for passing of the sewage water through an  effluent treatment plant before being diverted for irrigation in this area also as it is being passed through treatment plant in the  Jorbeer area of the city.
Keywords: Sewage water; sandy soils; vegetables